2022
DOI: 10.3329/ijarit.v11i2.57265
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and vegetative growth of pathogenic seed-borne fungus, Curvularia lunata of tomato and its in vitro control measures

Abstract: Present studies were conducted to isolate and identify the seed-borne pathogenic fungus from the selected tomato variety through morphological and molecular techniques based on the sequencing of internal transcribed spacer (ITS) region of 18S rDNA. According to the colony and conidial features, the fungus was identified as Curvularia sp. The obtained ITS sequencing showed above 99% similarity with Curvularia lunata in the NCBI database. The sequence of the fungus was deposited in NCBI GenBank under the accessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Our results conform to the findings of other researchers who reported propiconazole as an effective fungicide against Pestalotiopsis guepinii [28] [29]. It has been reported that fungicides Tilt 250EC and Amistar Top 325 SC were effective against the mycelium growth of Curvularia lunata [16].…”
Section: Effect Of Bio-control Agents and Fungicides On The Targeted ...supporting
confidence: 92%
See 1 more Smart Citation
“…Our results conform to the findings of other researchers who reported propiconazole as an effective fungicide against Pestalotiopsis guepinii [28] [29]. It has been reported that fungicides Tilt 250EC and Amistar Top 325 SC were effective against the mycelium growth of Curvularia lunata [16].…”
Section: Effect Of Bio-control Agents and Fungicides On The Targeted ...supporting
confidence: 92%
“…The efficacy of three different synthetic fungicides Tilt 250EC @ 100 ppm, 250 ppm and 500 ppm; and Ridomil gold MZ 68 WP and Amistar Top 325 SC @ 250 ppm, 500 ppm, and 750 ppm were evaluated on the isolated fungus by poison food techniques under laboratory conditions [16]. The PDA plate containing the tested fungus without any bio-control agent or fungicide was served as control.…”
Section: In Vitro Mycelial Growth Inhibition Of the Fungal Pathogenmentioning
confidence: 99%
“…The growth pattern of the isolated fungus was evaluated on different soil fungal culture media (potato dextrose agar, PDA), (potato sucrose agar, PSA), (carrot agar, CA), (Richard agar, RA), (Honey peptone agar, HPA), and (Honey agar, HA) as described by Mallik et al (2021). The response of different temperature conditions (15, 20, 25, 30 and 35°C) was evaluated for the vegetative growth of the isolated fungus as the method mentioned by Billah et al (2021). The five different pH conditions (5, 6, 7, 8 and 9) were used to assess the mycelial growth of the fungus (Sikder et al 2020).…”
Section: Effect Of Culture Media Temperature Ph and Light Of The Path...mentioning
confidence: 99%